Dynamics in a Delayed Neural Network Model of Two Neurons with Inertial Coupling. (16th August 2012) - Xu, Changjin; Li, Peiluan
Abstract : A delayed neural network model of two neurons with inertial coupling is dealt with in this paper. The stability is investigated and Hopf bifurcation is demonstrated. Applying the normal form theory and the center manifold argument, we derive the explicit formulas for determining the properties of the bifurcating periodic solutions. An illustrative example is given to demonstrate the effectiveness of the obtained results.